2017
DOI: 10.1111/jwas.12439
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Megalocytivirus Type 3 Infection with Low Mortality in Starry Flounder, Platichthys stellatus, in Korea

Abstract: MVSF-12 belonging to megalocytivirus type 3 was isolated from cultured starry flounder; Platichthys stellatus, at the moribund or subclinical stage with low mortalities in Korea. Of 20 apparently healthy fish in the farms, 17 were also confirmed in nested polymerase chain reaction to be infected by megalocytivirus. When starry flounder; rock bream, Oplegnathus fasciatus; and olive flounder, Paralichthys olivaceus, were artificially infected by MVSF-12 or iridovirus sachun-1 (IVS-1, megalocytivirus type 1), sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Moreover, it is known to show pathogenicity regardless of the environment and species when it infects a susceptible host (Lee et al, 2020). Our result demonstrated a different Megalocytivirusinfection in starry flounder compared to that in previous reports (Park et al, 2012;Won et al, 2013;Jung et al, 2016;Jin et al, 2018). Thus, starry flounder can be considered to show susceptibility to the RSIV and TRBIV genotypes.…”
Section: Evaluation Of Newly Designed Multiplex Pcr Using Field Samplescontrasting
confidence: 46%
See 2 more Smart Citations
“…Moreover, it is known to show pathogenicity regardless of the environment and species when it infects a susceptible host (Lee et al, 2020). Our result demonstrated a different Megalocytivirusinfection in starry flounder compared to that in previous reports (Park et al, 2012;Won et al, 2013;Jung et al, 2016;Jin et al, 2018). Thus, starry flounder can be considered to show susceptibility to the RSIV and TRBIV genotypes.…”
Section: Evaluation Of Newly Designed Multiplex Pcr Using Field Samplescontrasting
confidence: 46%
“…RSIV infection is a viral disease that causes massive mortality in rock bream mariculture. Recently, studies have reported the RSIV infection of turbot, olive flounder, and starry flounder (Takano et al, 2001;Shi et al, 2004;Jeong et al, 2005;Won et al, 2013;Jin et al, 2018).…”
Section: Evaluation Of Newly Designed Multiplex Pcr Using Field Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the analysis of viral infection level, each individual sample ( n = 20) was quantified with specific primer sets as published by Jin et al. (), targeting a fragment of the MCP region. This was carried out using the LightCycler 480II instrument (Roche, USA) according to the manufacturer's instructions.…”
Section: Pairwise Comparison Of Genetic Diversities Between Megalocytmentioning
confidence: 99%
“…Supplementary Materials: Supplementary materials can be found at http://www.mdpi.com/1422-0067/21/5/1707/ s1. References [95][96][97][98][99][100]…”
mentioning
confidence: 99%